Template‐Free Self‐Assembly of Dimeric Dicarbocyanine Dyes. Issue 33 (22nd November 2017) - Patlolla, Prathap Reddy; Mallajosyula, Sairam S.; Datta, Bhaskar
Abstract: Symmetrical dicarbocyanine dyes are known to cooperatively assemble on DNA templates. With the goal of developing dyes that are capable of template‐free self‐assembly, two N‐linked dimeric benzothiazole containing pentamethine cyanine dyes have been synthesized. UV‐visible spectroscopy of the dimeric dyes reveals very strong propensities for self‐assembly unlike their monomeric dye counterparts. The N‐propyl linked dye exhibits pronounced H‐aggregation at micromolar dye concentrations with the absorption maxima blue‐shifted by nearly 200 nm. In contrast, an N‐hexyl linked dye preferentially folds into H‐dimers. Similar aggregates of the monomeric dicarbocyanine dyes are known to be observed at much higher dye concentrations or in presence of suitable templates such as DNA molecules. The aggregate species of the dimeric dyes are identified based on shifts in their absorbance maxima and quenched fluorescence. The calculated electronic structure of the dimeric dyes supports their observed aggregation behaviour. Further, introduction of DNA molecules with AT‐tracts leads to transformation of the spontaneously formed dimeric dye H‐aggregates and H‐dimers into DNA‐bound dye species. Abstract : Dimeric dicarbocyanine dyes have been developed that are capable of self‐aggregation without the requirement of polymeric templates. The dimeric dyes self‐assemble into fluorescence quenched H‐dimers and H‐aggregates at micromolar concentrations, in sharp contrast to the cognate monomeric dyes. Disruption of the dimeric dye aggregates upon interaction with specific DNA duplexes suggests their use in fluorescence sensing applications.